ENHANCED CAESAR CIPHER ALGORITHM USING DYNAMIC KEY GENERATION WITH TIMESTAMP TECHNIQUE FOR DATA SECURITY - Rifqi , Muhammad; Ab Ghani, Hadhrami; Karimah, Hasyiya; Santoso, Hadi (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2026)
Data security remains a critical concern in the digital era due to the rising frequency of unauthorized access. While the Caesar Cipher is a foundational cryptographic technique, its static nature makes it highly vulnerable to frequency analysis and brute-force attacks. This study proposes an Enhanced Caesar Cipher algorithm that integrates Dynamic Key Generation utilizing a timestamp technique to improve data confidentiality. By generating keys dynamically based on the exact time of encryption, the algorithm ensures that the same plaintext results in different ciphertexts at different intervals, effectively mitigating basic substitution pattern recognition.Experimental results demonstrate that the proposed method maintains a lightweight computational profile, achieving an average encryption time of 0.3 seconds for a 1 MB file with a linear scaling pattern . This efficiency makes the algorithm particularly suitable for low-power environments, IoT applications, and educational purposes where modern complex encryption may be resource-prohibitive. While not intended to replace high-security standards like AES, this enhanced approach provides a significant security improvement over the traditional Caesar Cipher by introducing temporal variability into the key space.